2021
DOI: 10.1039/d1ce00220a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and thermodynamic investigation of Bi2M2+O4 (M = Pd, Cu)

Abstract: The work establishes a connection between the thermodynamics and crystal growth of Bi2M2+O4 and reveals new insights into the description and understanding of the growth process and its optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Figure 6 also clearly shows that excessive CuO phase precipitates at the grain boundaries as the amount of Cu ions exceeds the solubility limit of KNN when y ⩾ 1.5 mol%. The reported phase diagram 40,41) and previous studies on CuO doping in KNN 38,42) suggest that the CuO phase exists as a liquid phase under atmospheric oxygen partial pressure at 1020 °C-1060 °C at which the coarsening of the KNN single crystals have been observed. In general, the liquid phase present at grain boundaries accelerates grain growth through the promoting elemental diffusion.…”
Section: Sn1015-3mentioning
confidence: 68%
See 1 more Smart Citation
“…Figure 6 also clearly shows that excessive CuO phase precipitates at the grain boundaries as the amount of Cu ions exceeds the solubility limit of KNN when y ⩾ 1.5 mol%. The reported phase diagram 40,41) and previous studies on CuO doping in KNN 38,42) suggest that the CuO phase exists as a liquid phase under atmospheric oxygen partial pressure at 1020 °C-1060 °C at which the coarsening of the KNN single crystals have been observed. In general, the liquid phase present at grain boundaries accelerates grain growth through the promoting elemental diffusion.…”
Section: Sn1015-3mentioning
confidence: 68%
“…1 and 2 was not detected in the calcined powder. From the phase diagram of the CuO and Cu 2 O system, 40) Cu 2 O is likely to be generated above 1040 °C. Cu 2 O, which is formed by a partial phase transition of a large amount of CuO segregated near the crystal growth interface under elevated temperature, acts as the liquid phase, which promotes the crystal growth in the same manner as CuO.…”
Section: Sn1015-3mentioning
confidence: 99%
“…Most experimental articles describe phase diagrams for Bi 2 O 3 –CuO systems or similar two- or three-component systems. They all consider different stoichiometric mixtures and liquid phases, making it difficult to compare the same stability region of solid stoichiometric CBO.…”
Section: Resultsmentioning
confidence: 99%
“…Continuously, the melt must absorb O 2 (gas) from the atmosphere to facilitate the Me n /Me n+1 equilibrium in the melt, because the latter ion is permanently incorporated into the crystal. Possibly, this limits the maximum growth rate, but nevertheless, the growth of crystals with a high oxidation state, such as the initial example Ca 2 Fe 2 O 5 [29], or Bi 2 CuO 4 [44], is possible without severe problems. Figure 5b shows the opposite case where the average oxidation level of the crystal is lower than that of the melt.…”
Section: Discussionmentioning
confidence: 99%
“…With simultaneous DTA/TG measurements, it was found that melting is accompanied by a positive TG step, and the magnitude of this step ( 0.2%) is almost proportional to the oxygen concentration in the atmosphere during the measurement [40,41] 3+ 2 Pd 2+ O 4 , the mass rises, due to oxygen incorporation and partial oxidation of Cu + or Pd 0 to the two-valent state. Bi 2 CuO 4 single crystals up to 6 mm in diameter and 7 cm in length were obtained by OFZ [44].…”
mentioning
confidence: 99%